Enhancing Academic Writing Skills and Ethical Awareness among Sociology Department Students at Halu Oleo University through Reference Management Training - Hannin Pradita Nur Soulthoni; Dian Puspita Rizki; Anggun Tri Aksari (Universitas Muhammadiyah Malang, 2025)
The study aimed to assess the effectiveness of Mendeley training in improving reference management skills and academic ethics among students in the Sociology Department at Halu Oleo University. Specifically, the research focused on evaluating the impact of the training on students' ability to manage references efficiently and their understanding of academic ethics, particularly in avoiding plagiarism and adhering to proper citation practices. This outreach program involved 50 students, primarily final-year students preparing their theses and research reports. The training program, conducted from November 4 to December 4, 2024, included practical sessions on using Mendeley for reference management, alongside discussions on academic ethics, such as plagiarism prevention and proper citation practices. Data was collected through pre-test and post-test questionnaires, as well as observational analysis during hands-on sessions. The primary outcomes measured were students' understanding of Mendeley, reference management skills, and academic ethics before and after the training. Results showed significant improvements in all areas, with the percentage of students demonstrating a strong understanding of Mendeley, increasing from 30% to 85%, reference management skills from 25% to 80%, and academic ethics awareness from 40% to 85%. The findings underscore the effectiveness of practical, interactive training in enhancing both technical skills and ethical awareness, which can lead to higher-quality academic work. The study highlights the importance of integrating reference management training and academic ethics into community engagement initiatives, with the potential to improve the overall academic integrity of students’ scholarly work.